ANALISIS PENGARUH SISTEM PEMELIHARAAN DAN STRATEGI PEMASARAN TERHADAP PROFITABILITAS PADA USAHA KECIL MENENGAH (UKM) AGRIBISNIS SAPI POTONG KABUPATEN BOGOR - Eko Semobodo (Universitas 17 Agustus 1945 Jakarta, 2018)
Bogor Regency is one of potential livestock development areas in West Java Province. The opportunity for beef cattle development is quite large, it is influenced by several factors such as the availability of large quantities of cattle and relatively good quality, the availability of sufficient cattle feed, the availability of food land, the relatively easy access to marketing, adequate farmers skills, socio-cultural Support and support from either the private sector or the government. The purpose of this study is to know how the effect of beef cattle raising system on business profitability, How is the influence of beef cattle marketing strategy on business profitability, and How is the influence of maintenance system and marketing strategy of beef cattle to profitability of business. This research is done through descriptive approach of quantitative and qualitative with research design using Sequential Explanatory Strategy design. This research was conducted in Babakan Madang Subdistrict, Gunung Pancar, Bogor Regency. Research Time started from March to July 2017. The population in this study is the perpetrators of cattle breeder SME Subdistrict Babakan Madang, Mount Pancar, Bogor Regency. The sample of this research is 63 perpetrators of cattle breeder UKM. Technique Determination of sample using Non Probability sampling which met by chance in accordance with criteria (accidental sampling). Technical Analysis used in this research is Quantitative and Qualitative Descriptive Analysis. The result of the research shows that 1) Maintenance System has positive effect to Profitability of Business, with tcount is bigger than ttable, where (3,276> 1,668). 2) Marketing Strategy has a negative effect on business profitability. Can be seen tcount value is smaller than ttable, where (0,805 <1,668). 3). Maintenance System and Marketing Strategy together have a significant influence on Profitability of Business, while the value of influence or correlation coefficient (r) 0.390 means that between the maintenance system and marketing strategy has a low correlation based on perceptions of business profitability. While the contribution given by the value of determination coefficient (R2) of 0.152 or 15.2% and the remaining 84.8% influenced by other factors outside of this research variables.